Extensive rectovaginal space hematoma causing urine retention as a complication of vaginoplasty: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Rectovaginal space hematoma following vaginoplasty is a rare complication that canlead to serious morbidity and disability. In the literature, reported cases remain few, especially inlow-income countries where cosmetic gynecology consultations are increasing.Case presentation: We present a case of extensive rectovaginal space hematoma presenting withurine retention following vaginoplasty. The patient had anemia, hypotension, tachycardia, vulvalswelling, and a suprapubic mass from the overdistend bladder. She was surgically managed and didwell postoperatively.Conclusion: Rectovaginal space hematomas are rare and associated with significant morbidity ifinappropriately managed. Cosmetic gynecological surgeons should be aware of this complication.